Electromechanical Coupling in the Hyperpolarization-Activated K(+) Channel KAT1 - Clark, Michael David (Nature, 2020)
Voltage-gated potassium (K(v)) channels orchestrate electrical signaling and control cell volume by gating in response to either membrane depolarization or hyperpolarization. Yet, while all voltage-sensing domains transduce transmembrane electric field changes by a common mechanism involving the outward or inward translocation of gating charges(1–3), the general determinants of channel gating polarity remain poorly understood(4). Here, we suggest a molecular mechanism for electromechanical coupling and gating polarity in non-domain-swapped K(v) channels based on the cryo-EM structure of KAT1, the hyperpolarization-activated K(v) channel from Arabidopsis thaliana. KAT1 displays a depolarized voltage sensor, which interacts with a closed pore domain directly via two interfaces and indirectly via an intercalated phospholipid. Functional evaluation of KAT1 structure-guided mutants at the sensor-pore interfaces suggests a mechanism in which direct interaction between the sensor and C-linker hairpin in the adjacent pore subunit is the primary determinant of gating polarity. We suggest that a ~5–7 Å inward motion of the S4 sensor helix can underlie a direct-coupling mechanism, driving a conformational reorientation of the C-linker and ultimately opening the activation gate formed by the S6 intracellular bundle. This direct-coupling mechanism contrasts with allosteric mechanisms proposed for hyperpolarization-activated cyclic nucleotide-gated (HCN) channels(5), and may represent an unexpected link between depolarization and hyperpolarization-activated channels.